2020
DOI: 10.1002/anie.202000545
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemically Driven Cation Exchange Enables the Rational Design of Active CO2Reduction Electrocatalysts

Abstract: Metal oxides or sulfides are considered to be one of the most promising CO2 reduction reaction (CO2RR) precatalysts, owing to their electrochemical conversion in situ into highly active electrocatalytic species. However, further improvement of the performance requires new tools to gain fine control over the composition of the active species and its structural features [e.g., grain boundaries (GBs) and undercoordinated sites (USs)], directly from a predesigned template material. Herein, we describe a novel elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 59 publications
0
47
0
Order By: Relevance
“…[133] The formed biphasic catalyst coupled with inter-particle GBs and undercoordinated sites are the active sites and modulate the binding energies to the intermediates produced in CO 2 RR. [134] Though it was reported that Cu electrodes derived from the reduction of thick Cu 2 O films exhibit high FE toward CO and formate formation at low overpotentials, [135] the Cu particles with GB structures in the oxide-derived Cu catalysts possess strengthen binding sites for further hydrogenation of *CO into hydrocarbons. [136,137] However, some reports shows that oxidized Cu catalysts favor for electrochemical CO 2 RR to C 2 products, rather than to CH 4 .…”
Section: Cu-based Compound For Ch 4 Formationmentioning
confidence: 99%
“…[133] The formed biphasic catalyst coupled with inter-particle GBs and undercoordinated sites are the active sites and modulate the binding energies to the intermediates produced in CO 2 RR. [134] Though it was reported that Cu electrodes derived from the reduction of thick Cu 2 O films exhibit high FE toward CO and formate formation at low overpotentials, [135] the Cu particles with GB structures in the oxide-derived Cu catalysts possess strengthen binding sites for further hydrogenation of *CO into hydrocarbons. [136,137] However, some reports shows that oxidized Cu catalysts favor for electrochemical CO 2 RR to C 2 products, rather than to CH 4 .…”
Section: Cu-based Compound For Ch 4 Formationmentioning
confidence: 99%
“…Recently, Hod's group prepared a Cu 2 O@CoS x electrocatalyst using an electrochemically driven cation exchange method. [ 82 ] The rich grain boundaries and under‐coordinated sites acted as active species during CO 2 RR, exhibiting a CO 2 ‐to‐formate FE greater than 87%.…”
Section: Metal‐based Electrocatalystsmentioning
confidence: 99%
“…Since the discovery of graphene in 2004, two‐dimensional (2D) materials have been attracted huge research attentions due to their unique physical, optical and electrical properties so as to many highly promising applications [1] . Apart from extensively investigated 2D materials such as g‐C 3 N 4 , layered double hydroxides (LDH), transition‐metal dichalcogenides (TMDs), and hexagonal boron nitride (h‐BN), [2–5] the 2D metal–organic frameworks (MOFs) comprised of metal centers and organic linkers have aroused emerging interests in materials and catalysis [6–13] . Because of their extraordinarily high surface areas, tunable pore size and regulable internal surface, MOFs have been widely applied in many fields, such as electrocatalysis [14–17] .…”
Section: Figurementioning
confidence: 99%
“…[1] Apart from extensively investigated 2D materials such as g-C 3 N 4 , layered double hydroxides (LDH), transition-metal dichalcogenides (TMDs), and hexagonal boron nitride (h-BN), [2][3][4][5] the 2D metal-organic frameworks (MOFs) comprised of metal centers and organic linkers have aroused emerging interests in materials and catalysis. [6][7][8][9][10][11][12][13] Because of their extraordinarily high surface areas, tunable pore size and regulable internal surface, MOFs have been widely applied in many fields, such as electrocatalysis. [14][15][16][17] To date, the most reported method for synthesizing 2D MOF NSs was ultrasonication and solvo-thermal method.…”
mentioning
confidence: 99%